The effect of leg kick on sprint front crawl swimming - Gourgoulis, V.; Boli, A.; Aggeloussis, N.; Toubekis, A.; Antoniou, P.; Kasimatis, P.; Vezos, N.; Michalopoulou, M.; Kambas, A.; Mavromatis, G. (Journal of Sports Sciences, 2014)
The aim of this study was to examine the influence of leg kick on the pattern, the orientation and the propulsive forces produced by the hand, the efficiency of the arm stroke, the trunk inclination, the inter-arm coordination and the intra-cyclic horizontal velocity variation of the hip in sprint front crawl swimming. Nine female swimmers swam two maximal trials of 25 m front crawl, with and without leg kick. Four camcorders were used to record the underwater movements. Using the legs, the mean swimming velocity increased significantly. On the contrary, the velocity and the orientation of the hand, the magnitude and the direction of the propulsive forces, as well as the Froude efficiency of the arm stroke were not modified. The hip intra-cyclic horizontal velocity variation was also not changed, while the index of coordination decreased significantly. A significant decrease (13%) was also observed in the inclination of the trunk. Thus, the positive effect of leg kick on the swimming speed, besides the obvious direct generation of propulsive forces from the legs, could probably be attributed to the reduction of the body`s inclination, while the generation of the propulsive forces and the efficiency of the arm stroke seem not to be significantly affected.